The Impact of an Accountability Intervention with Diagnostic Feedback : Evidence from Mexico - de Hoyos, Rafael; Garcia-Moreno, Vicente A.; Patrinos, Harry Anthony (World Bank, Washington, DC, 2015)
In 2009, the Mexican state of Colima implemented a low-stakes accountability intervention with diagnostic feedback among 108 public primary schools with the lowest test scores in the national student assessment. A difference-in-difference and a regression discontinuity design are used to identify the effects of the intervention on learning outcomes. The two alternative strategies consistently show that the intervention increased test scores by 0.12 standard deviations only a few months after the program was launched. When students, teachers, and parents in a school know that their scores are low, and this triggers a process of self-evaluation and analysis, the process itself may lead to an improvement in learning outcomes. Information on quality, without punitive measures but within a supportive and collaborative environment, appears to be sufficient to improve learning outcomes.